Pengaruh Bubur Pisang Isomaltosa-oligosakarida dan Fibercreme terhadap Kadar Glukosa dan Lipida Darah serta Profil Digesta Tikus Diabetes - Yustinus Marsono; Priyanto Triwitono; Elisabeth Desy Arianti; Hendrik Gunawan; Rochmad Indrawanto (agriTECH, 2020)
Dietary fiber and resistant starch are known to be beneficial in lowering both glucose and lipid concentration in human. Fibercreme, a fiber rich product has been developed. It is a commercial non-dairy creamer that uses various oligosaccharides such as Isomaltose-oligosaccharides (IMO) or inulin as fiber source to replace the glucose component of conventional creamer. In this study, IMO and fibercreme were used to replace sucrose of the banana porridge. Therefore, the purpose of this study was to determine porridge effects on glucose, triglyceride, serum cholesterol and digesta profile in diabetic STZ-NA induced rats. Twenty-five male Wistar rats were divided into five groups and fed four different diets including the standard (KS and KN), banana porridge with sweetener IMO (BP+IMO), fibercreme (BP+FC) and (BP + Sukrosa). In these diets, porridge subtituted 30% energy of the standard diet, and the intervention was conducted for 28 days. It was found that banana-IMO porridge showed the lowest decrease in serum glucose level with 56.09%, followed by banana-fibercreme (47.61%) and bananasucrose (36.61%). Furthermore, similar trend was found in their cholesterol-lowering effects with 36.82%, 25.68% and 7.86% respectively. However, triglyceride level effects were highest in banana-IMO porridge (9.06%), followed by banana-sucrose (6.47%) and banana-fibercreme (3.72%). In addition, sucrose replacement with IMO increases weight and water content, as well as decrease caecal digesta pH. However, fibercreme increases only water content and does not decrease caecal digesta pH.